Association of glucagon-to-insulin ratio and nonalcoholic fatty liver disease in patients with type 2 diabetes mellitus. (March 2019) - Moh Moh, Myint Aung; Jung, Chan-Hee; Lee, Bora; Choi, Dughyun; Kim, Bo-Yeon; Kim, Chul-Hee; Kang, Sung-Koo; Mok, Ji-Oh
Objective: The aim of this study is to investigate the association between glucagon-to-insulin ratio and the presence of nonalcoholic fatty liver disease on ultrasonography in participants with type 2 diabetes mellitus. Research design and methods: This cross-sectional study was performed with data obtained from 172 participants with type 2 diabetes mellitus admitted to a University hospital of Korea. Participants were assessed for serum fasting and postprandial serum glucagon-to-insulin ratio and divided into tertiles. Nonalcoholic fatty liver disease was defined as ultrasonographically detected fatty liver. Results: Prevalence of nonalcoholic fatty liver disease was significantly decreased across tertile of fasting and postprandial glucagon-to-insulin ratio ( p = 0.009 for trend, p = 0.001 for trend, respectively). Lower glucagon-to-insulin ratio was significantly associated with the presence of nonalcoholic fatty liver disease even after adjustment for potential confounding variables [fasting glucagon-to-insulin ratio: odds ratio (95% confidence interval), 2.68 (1.08–6.86)], postprandial glucagon-to-insulin ratio: [2.72 (1.03–7.35)]. The participants in the lowest tertile of fasting glucagon-to-insulin ratio had higher body mass index, visceral fat thickness, subcutaneous fat thickness, homeostasis model assessment–insulin resistance and shorter duration of diabetes mellitus. Conclusion: This study suggests that lower glucagon relative insulin may be independently associated with nonalcoholic fatty liver disease in participants with type 2 diabetes.